2015
DOI: 10.1016/j.hlc.2015.06.790
|View full text |Cite
|
Sign up to set email alerts
|

Country access to cardiac health (CATCH) program: improving rehospitalisation rates and length of stay for cardiac rehabilitation using innovative telehealth delivery

Abstract: S453 Conclusion:Increased physician awareness about the benefits of CR is required and initiatives to overcome barriers to referral may improve the delivery of evidence-based care.http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Whereby the patient's referral is forwarded nursing staff to the central referral point for CATCH and directed to the NP‐led programme. The central CATCH referral point has been shown previously (Tideman et al, ; Wilson, Peng, Clark, & Tirimacco, ) to be very successful in improving coordination of CR by providing a central referral point for all South Australians patients. Tideman et al () data outcomes demonstrated improved referral rates, less hospital admissions and shorter lengths of stay.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereby the patient's referral is forwarded nursing staff to the central referral point for CATCH and directed to the NP‐led programme. The central CATCH referral point has been shown previously (Tideman et al, ; Wilson, Peng, Clark, & Tirimacco, ) to be very successful in improving coordination of CR by providing a central referral point for all South Australians patients. Tideman et al () data outcomes demonstrated improved referral rates, less hospital admissions and shorter lengths of stay.…”
Section: Discussionmentioning
confidence: 99%
“…The central CATCH referral point has been shown previously (Tideman et al, ; Wilson, Peng, Clark, & Tirimacco, ) to be very successful in improving coordination of CR by providing a central referral point for all South Australians patients. Tideman et al () data outcomes demonstrated improved referral rates, less hospital admissions and shorter lengths of stay. Grace et al () reported the impact of an automatic referral to CR combined with a telephone call from a liaison nurse prior to the initial CR appointment increased patient CR participation from 50% to 78%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In 2013, the network started the Country access to cardiac health (CATCH) program to improve secondary prevention after postacute care. 10 Both programs have been effective: the difference in cardiac mortality after an acute event between rural and metropolitan areas was eliminated by 2010, and there was a substantial reduction in readmissions of patients from rural areas.…”
Section: Key Pointsmentioning
confidence: 99%